Romantisme Anak Muda dalam Lagu-Lagu Ambon - Kadir, Hatib Abdul (Jurnal Ilmu Komunikasi, 2008)
Abstract: This writing discusses about Ambonese youth romanticism that is mediated through local songs in cassette and VCD. For Ambonese lyouth, Indonesian populer sogs alsa have the same position as Ambonese local songs which are growing and almost always have new groups or singers every year. The most favorite song that Ambonese youth like most is romantic song. The construction of romanticsm presents through the personification of loving their parents, their lover and their homeland which is then extended to wider solidariy such as nationalism and similar religion. The substance of romanticism in the Ambonese songs aso experience changing since the 1999-2003 riots in Ambon. However, the romantic songs could becone means to neutralize the issue of segregation of religion because the love for mother and Ambon as their homeland is belongs to everyone and cannot be defeated by any kind of sentiments.